2019
DOI: 10.1021/acsami.9b09564
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Lattice Strain and Efficiency for Sn-Perovskite Solar Cells

Abstract: In the composition of Q0.1(FA0.75MA0.25)0.9SnI3, Q is replaced with Na+, K+, Cs+, ethylammonium+ (EA+), and butylammonium+ (BA+), respectively, and the relationship between actually measured lattice strain and photovoltaic performances is discussed. The lattice strain evaluated by the Williamson–hall plot of X-ray diffraction data decreased as the tolerance factor was close to one. The efficiency of the Sn-perovskite solar cell was enhanced as the lattice strain decreased. Among them, EA0.1(FA0.75MA0.25)0.9SnI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 37 publications
5
105
0
Order By: Relevance
“…[34] When 0.1 mm EDA was coated on the surface of the perovskite, both the HOMO and LUMO energy have shifted to the deeper energy states indicating the decrease in self-doping as explained previously. [35,36] Interestingly, with the coating of 0.1 mm EDA, the E f has shifted to a value of −4.78 eV which is shallower than E i (−5.0 eV) indicating the n-type character of the film. [34] This change in semiconducting nature can be assigned to the increase in electron concentration contributed by the electron-donating amine group of EDA at the perovskite surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] When 0.1 mm EDA was coated on the surface of the perovskite, both the HOMO and LUMO energy have shifted to the deeper energy states indicating the decrease in self-doping as explained previously. [35,36] Interestingly, with the coating of 0.1 mm EDA, the E f has shifted to a value of −4.78 eV which is shallower than E i (−5.0 eV) indicating the n-type character of the film. [34] This change in semiconducting nature can be assigned to the increase in electron concentration contributed by the electron-donating amine group of EDA at the perovskite surface.…”
Section: Resultsmentioning
confidence: 99%
“…We also investigated the strain component (C ε ) and Urbach energy (E u ) in the perovskite film after insertion of Br anion by using Williamson-Hall plot (Figure S14a-d, Supporting Information) and absorption spectra (Figure S14e, Supporting Information) as reported in some of the recent articles. [5,11,36] The larger value of C ε and E u are an indication of the presence of large traps within the perovskite. Hence, with the optimized concentration of Br 2.5 mol% the values of C ε (0.0755) and E u (0.091 eV) were least among all the perovskite films, supporting the best performance of PSCs based on Br-2.5% compared to other Br added solar cells (Figure S14f, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…It is found that as the tolerance factor t gets closer to 1, the lattice strain of Sn‐based MHPs gradually decreases due to the formation tendency of the cubic crystal structure (Figure 3c,d). [ 37 ] Because the carrier mobility increases as the lattice strain decreases, the increased lattice strain, when t value gets away from 1, will decrease the carrier mobility and reduce the PCE of the corresponding PSCs (Figure 3e). Notably, by optimizing the t value to be close to 1 using EA, PSCs based on EA 0.1 (FA 0.75 MA 0.25 ) 0.9 SnI 3 film with the lowest lattice strain shows a champion PCE of 5.41%.…”
Section: Strain Engineering In Mhps and Their Pscsmentioning
confidence: 99%
“…Meanwhile, the effect of strain on the optoelectronic properties and ion migration of MHPs has also been investigated. [ 152–167 ] Zhao et al. discovered that lattice strain significantly affects the stability of MHPs ( Figure a) via modifying the activation energy of ion migration; [ 152 ] a larger lattice strain reduces the activation of ion migration, promoting the degradation of CH 3 NH 3 PbI 3 films.…”
Section: Ferroicity Strain and Optoelectronic Performancementioning
confidence: 99%